Bagaimana readiness dosen dalam transformasi teknologi pembelajaran? Tinjauan berdasarkan psychological capital dan generasi: How is lecturers' readiness for the transformation of learning technology? A review based on psychological capital and generation - Abdul Fattah; Amalia, Rahmatika Sari; Elok Faiz Fatma El Fahmi; Hilda Halida (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2025)
Today's learning technologies must be mastered by lecturers in order to support the progress of quality education. Therefore, lecturers are expected to be able to adapt to existing changes, especially in the use of learning technology. The purpose of this study is to determine the effect of psychological capital on readiness to change, moderated by Generation X and Y groups. The method used in this study is explanatory quantitative research where research data was collected using Psychological Capital Scale (ω=0,847) and Readiness to Change Scales (ω=0,939) given to 267 lecturers in Indonesia. The results of this study were analysed using the JASP regression test and the R moderation test. The results showed that psychological capital is able to influence lecturers' readiness to change in using learning technology. However, generation has not been proven to moderate the strong and weak influence of psychological capital on the readiness to change lecturers in utilizing learning technology. This is because each generational group has unique characteristics in terms of psychological capital.